Front Cover Image: Volume 3 Issue 2. Issue 2 (28th June 2022) - Liu, Yuan; Chen, Ning; Li, Weidong; Sun, Mingzi; Wu, Tong; Huang, Bolong; Yong, Xue; Zhang, Qinghua; Gu, Lin; Song, Haoqiang; Bauer, Robert; Tse, John S.; et al.
Abstract : Front cover image : Ruthenium‐based electrocatalysts have great potential as an alternative to platinum‐based materials for the electrolysis of water for hydrogen evolution. In this work, a unique two‐site mechanism of the ruthenium single/dual atoms and Ru nanoclusters to strengthen the stability of single atom sites and enhance its intrinsic activity was identified. Ru S/DAs and Ru NCs demonstrate high electroactivity due to the electroactive Ru 4 d orbitals. The introduction of Ru NCs activates the carbon support, providing a high electronic conductivity to transfer electrons from Ru NCs to Ru S/DAs, and facilitates water dissociation for the HER process. (DOI: 10.1002/smm2.1067 )